Primary unilateral cleft lip repair - H. S. Adenwalla; P. V. Narayanan (Indian Journal of Plastic Surgery)
The unilateral cleft lip is a complex deformity. Surgical correction has evolved from a straight repair through triangular and quadrilateral repairs to the Rotation Advancement Technique of Millard. The latter is the technique followed at our centre for all unilateral cleft lip patients. We operate on these at five to six months of age, do not use pre-surgical orthodontics, and follow a protocol to produce a notch-free vermillion. This is easy to follow even for trainees. We also perform closed alar dissection and extensive primary septoplasty in all these patients. This has improved the overall result and has no long-term deleterious effect on the growth of the nose or of the maxilla. Other refinements have been used for prevention of a high-riding nostril, and correction of the vestibular web.